Classification of plastic surgery malpractice complaints brought before the São Paulo Medical Board that were treated as professional-misconduct cases: a cross-sectional study - Mariani, Paulo Cézar; Constantino, Clóvis Francisco; Nunes, Rui (São Paulo Medical Journal, 2020)
BACKGROUND: Nowadays, there is an ethical and moral necessity to establish rules that govern professional attitudes and conduct. In the medical field, these rules are multifaceted, given the health consequences inherent to medical procedures. Ethics is an even more delicate subject when it comes to plastic surgery, since one of the aims of this particular medical specialty is esthetic improvement of the body. OBJECTIVE: To survey and classify São Paulo State Medical Board investigations of plastic-surgery complaints that were treated as professional-misconduct cases between 2007 and 2016. DESIGN AND SETTING: Cross-sectional study conducted in a medical council. METHODS: A total of 360 cases were reviewed. Among these, 8 (2.23%) were dismissed, 1 (0.27%) became an administrative lawsuit and 351 (97.50%) were treated as professional-misconduct cases. RESULTS: A breakdown of the complaints filed over the nine-year period showed that complaints concerning malpractice were the most common (28.43%), followed by those regarding medical advertising (24.19%) and poor doctor-patient relationships (10.39%). CONCLUSION: Overall, the number of complaints lodged decreased over the last two years reviewed, although complaints regarding malpractice and poor doctor-patient relationships increased by 10% over the same period. In order to further reduce the number of medical board investigations, the medical establishment needs to carefully review the medical training of students and doctors at every stage of their careers.